Emerging trends in functional materials for electrochemical sensors in nicotine determination - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Yiu, Pang Hung; Boonyuen, Supakorn; Andou, Yoshito (Springer, 2024)
In the past year, there has been significant progress in the utilization of electrochemical strategies for the determination of harmful substances. Among those, the electrochemical determination of nicotine (NIC) has continued to be of significant interest ascribed to the global health concern of e-cigarette products, nowadays. Electrochemical sensors have become promising tools for the detection of NIC ascribed to their high sensitivity, selectivity, and ease of use. This review article provides a concise overview of the advanced developments in electrochemical sensors for NIC detection using modified functional materials such as carbon-based materials, metal–organic frameworks (MOF), MXene, polymer, and metallic based modifiers. The sensitivity of electrochemical sensors can be improved by modifying them with these conductive materials ascribed to their physical and chemical properties. The review also addresses the challenges and future perspectives in the f ield, including sensitivity and selectivity improvements, stability and reproducibility issues, integration with data analysis techniques, and emerging trends. In conclusion, this review article may be of interest to researchers intending to delve into the development of functional electrochemical sensors in future studies.